Neurocognitive function and quality of life after proton beam therapy for brain tumour patients. (February 2020) - Dutz, Almut; Agolli, Linda; Bütof, Rebecca; Valentini, Chiara; Baumann, Michael; Lühr, Armin; Löck, Steffen; Krause, Mechthild
Highlights: Proton therapy spares normal brain tissue from dose and may preserve neurocognition and quality of life. Self-reported and objectively measured neurocognition remained largely stable over time after proton therapy. The majority of MoCA subitems correlated to quality of life items regarding neurocognition. Abstract: Background: Neurocognitive function of adult patients with brain tumours may deteriorate after radiotherapy. Proton beam therapy (PBT) reduces the volume of irradiated healthy brain tissue and could potentially preserve neurocognition and quality of life (QoL). As present data are still limited, the impact of clinical factors and dosimetric parameters on neurocognitive function and QoL during recurrence-free follow-up after PBT is investigated. Methods: The current study includes 62 brain tumour patients treated with PBT between 2015 and 2017. Neurocognition and QoL were assessed at baseline and every 3 months after PBT using the Montreal Cognitive Assessment (MoCA) test together with EORTC-QLQ-C30 and BN20 questionnaires, respectively. Objective and self-reported measures of neurocognitive functions were correlated. During two years of follow-up, the impact of clinical co-factors as well as dosimetric parameters of several brain structures were analysed using a mixed-model approach. Results: At baseline, mean MoCA total score was 24.8/30 and self-reported cognitive function was 68.9/100. Both remained stable over time. Patients with impaired neurocognition on the MoCA test reported significantly lower global health status, cognitive, physical and role function as well as more fatigue, pain, headache and communication deficits compared to normal performing patients. For most follow-up time points, the majority of MoCA subitems correlated significantly to QoL items regarding neurocognition. Slight deterioration of the MoCA score was associated with tumours located in the left hemisphere and with an increase in relative volume of the anterior cerebellum that received doses of 30–40 Gy(RBE). Conclusion: Self-reported and objectively measured neurocognition and most other QoL domains remained largely stable over time during recurrence-free follow-up for brain tumour patients treated with PBT. The association between reduced cognitive function and irradiated volume of the anterior cerebellum requires validation in larger studies and comparison to patients treated with photon therapy.